On One Nonlocal Problem with Free Boundary - Berezovsky, A. A.; Mitropolskiy, Yu. A.; Netesova, T. M.; Березовский, А. А.; Митропольский, Ю. А.; Нетесова, Т. М.; Березовский, А. А.; Митропольский, Ю. А.; Нетесова, Т. М. (Institute of Mathematics, NAS of Ukraine, 2001)
We investigate group-theoretic properties of a nonlocal problem with free boundary for a degenerating quasilinear parabolic equation. We establish conditions for the invariant solvability of this problem, perform its reduction, and obtain an exact self-similar solution.